STEM-based Module Outline, Validity, Readability and Response towards Layout, Content and Utility Aspect. - A. Utami; P. Astuti; A. P. Sandi (Journal of Science Education Research, 2023)
In the 21st century of technology and the digital era, the integration of science, technology, engineering and mathematics in educational, political and economical is becoming an integral part. The implementation of STEM in the learning context should be followed by the readiness of teacher capability and supported by STEM-based teaching materials. This paper implements Design and Development Research (DDR) which followed the six stages to produce a STEM-based module for 7th graders, particularly on earth's structure and its dynamic topic. The developed STEM-based module follows the basic national competence for secondary level, module criteria, criteria of great STEM learning materials, STEM literacy practices and Engineering Design Process from NGSS and NRC (2010), OECD (2016), NAEP (2014) and National Kurikulum 2013. The questionnaire is delivered to experts, teachers and students to test the validity and readability of the STEM-based module. Moreover, it is also implemented as a learning module in one class of 7th graders in SMP Negeri 03 Soreang, which consists of 32 students. The results show that STEM-based module is valid to be used by high school students. Moreover, the readability score reaches 88.39%, while the response towards layout, content and utility aspects is 94.44% means that it had a minor revision.